(untitled) (International Journal of Engineering and Computer Science, 2014)
Distributed Denial-of-Service (DDoS) attack is a major threat for Internet applications. DDoS attacks relay on interrupting the services of a host connected to the Internet. In computer networks, a proxy server act as an intermediate server for bypassing the HTTP requests from clients to web servers. Client can access web server through different proxies. A novel attack detection scheme is proposed to prevent http attacks in web proxy based network. Here the attack detection is carried out at server. Accurate attack detection at server is difficult if proxy hide the information of clients. In the proposed scheme the detection is client based rather than proxy based. Here the client information is also passed along with the request so the server can easily identify the client and the attack detection become more accurate. This scheme utilizes locality behaviours such as Temporal and Spatial Localities(TSL) of proxy to server traffic.